Beta Amyloid Differently Modulate Nicotinic and Muscarinic Receptor Subtypes which Stimulate in vitro and in vivo the Release of Glycine in the Rat Hippocampus - Zappettini, Stefania; Grilli, Massimo; Olivero, Guendalina; Mura, Elisa; Preda, Stefania; Govoni, Stefano; Salamone, Alessia; Marchi, Mario (Frontiers in Pharmacology, 2012)
Using both in vitro (hippocampal synaptosomes in superfusion) and in vivo (microdialysis) approaches we investigated whether and to what extent β amyloid peptide 1–40 (Aβ 1–40) interferes with the cholinergic modulation of the release of glycine (GLY) in the rat hippocampus. The nicotine-evoked overflow of endogenous GLY in hippocampal synaptosomes in superfusion was significantly inhibited by Aβ 1–40 (10 nM) while increasing the concentration to 100 nM the inhibitory effect did not further increase. Both the Choline (Ch; α7 agonist; 1 mM) and the 5-Iodo-A-85380 dihydrochloride (5IA85380, α4β2 agonist; 10 nM)-evoked GLY overflow were inhibited by Aβ 1–40 at 100 nM but not at 10 nM concentrations. The KCl evoked [3H]GLY and [3H]Acetylcholine (ACh) overflow were strongly inhibited in presence of oxotremorine; however this inhibitory muscarinic effect was not affected by Aβ 1–40. The effects of Aβ 1–40 on the administration of nicotine, veratridine, 5IA85380, and PHA543613 hydrochloride (PHA543613; a selective agonist of α7 subtypes) on hippocampal endogenous GLY release in vivo were also studied. Aβ 1–40 significantly reduced (at 10 μM but not at 1 μM) the nicotine-evoked in vivo release of GLY. Aβ 1–40 (at 10 μM but not at 1 μM) significantly inhibited the PHA543613 (1 mM)-elicited GLY overflow while was ineffective on the GLY overflow evoked by 5IA85380 (1 mM). Aβ 40–1 (10 μM) did not produce any inhibitory effect on nicotine-evoked GLY overflow both in the in vitro and in vivo experiments. Our results indicate that (a) the cholinergic modulation of the release of GLY occurs by the activation of both α7 and α4β2 nicotinic ACh receptors (nAChRs) as well as by the activation of inhibitory muscarinic ACh receptors (mAChRs) and (b) Aβ 1–40 can modulate cholinergic evoked GLY release exclusively through the interaction with α7 and the α4β2 nAChR nicotinic receptors but not through mAChR subtypes.